1997
DOI: 10.1161/01.hyp.30.4.773
|View full text |Cite
|
Sign up to set email alerts
|

Essential Hypertension in African Caribbeans Associates With a Variant of the β 2 -Adrenoceptor

Abstract: Populations of West African ancestry dwelling in Western communities exhibit greater prevalence of human essential hypertension and higher rates of end-organ damage. The sympathetic nervous system influences cardiac output, vascular tone, renal sodium reabsorption, and renin release and could be implicated in enhanced vascular responsiveness observed in African hypertensives. Such an effect could arise from genetic variants that alter agonist response of alpha-adrenoceptors, leading to enhanced vasoconstrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 13 publications
3
78
2
3
Order By: Relevance
“…Finally, the 164Ile variant of the ADRB2 is associated with a decreased native adipocyte receptor function. 14 Although several previous reports have described associations between these polymorphisms and hypertension or obesity, [15][16][17][18][19][20] few studies have taken into account both variables in the same design. To our knowledge, this is the most extensive work done analyzing these polymorphisms and blood pressure and obesity phenotypes both as continuous and dichotomous variables in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the 164Ile variant of the ADRB2 is associated with a decreased native adipocyte receptor function. 14 Although several previous reports have described associations between these polymorphisms and hypertension or obesity, [15][16][17][18][19][20] few studies have taken into account both variables in the same design. To our knowledge, this is the most extensive work done analyzing these polymorphisms and blood pressure and obesity phenotypes both as continuous and dichotomous variables in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…The β2AR polymorphisms accounted for ∼2% of the observed variation in blood pressure (Bray et al 2000). While results of some groups confirmed the association between the 16Gly allele and blood pressure (Kotanko et al 1997;Rosmond et al 2000;Gratze et al 1999), others found opposite effects, i.e., an association between the 16Arg allele and hypertension (Busjahn et al 2000;Bengtsson et al 2001a,b;Timmermann et al 1998) or no effects at all (Herrmann et al 2002;Kato et al 2001;Xie et al 2000; for a recent meta-analysis see Hahntow et al 2006). Again, differing inclusion of haplotypes, variations in ethnicities and different study designs may contribute to these sobering results.…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 98%
“…It was found that the Gly16 allele was more common in hypertensive subjects than in normotensive African-Caribbean controls. Because the Gly16 allele directs an increased propensity for depressed regulation of the receptor, there is a possibility that an impaired vasodilatation in peripheral arteries in response to β 2 AR agonists may play a role in the hypertension of individuals carrying the Gly16 allele [20].…”
Section: Beta-1-adrenergic Receptor (β L -Ar) Blockersmentioning
confidence: 99%